A novel method for objective identification of 3-D potential vorticity anomalies - Implementation - Fischer, Christoph; Fink, Andreas H.; Schömer, Elmar; Van der Linden, Roderick; Maier-Gerber, Michael; Rautenhaus, Marc; Riemer, Michael (Zenodo, 2021)
This archive contents the source code of the strategy to objectively identify Potential Vorticity anomalies in 2-D and 3-D. It is part of the open-source framework "enstools" (https://github.com/wavestoweather/enstools), and realized as a module therein. The file enstools/feature/identification/pv_streamer/run_identify.py contains ausage example. An in-depth description and evaluation are done in the corresponding study, anotherarchived supplement provides 3-D visualizations of results. The research leading to these results has been accomplished within the project C3 "Predictability of tropical and hybrid cyclones over the North Atlantic Ocean" of the Transregional Collaborative Research Center SFB/TRR 165 "Waves to Weather" funded by the German Science Foundation (DFG).